Time- and Region-specific Effect of Vortioxetine on Central LPS-induced Transcriptional Regulation of NLRP3 Inflammasome - Ciani, Miriam; Rigillo, Giovanna; Benatti, Cristina; Pani, Luca; Blom, Johanna M.C.; Brunello, Nicoletta; Tascedda, Fabio; Alboni, Silvia (Current Neuropharmacology, 2025)
BackgroundInflammasome overactivation, multiprotein complexes that trigger inflammatory responses, plays a critical role in Major Depressive Disorder (MDD) pathogenesis and treatment responses. Indeed, different antidepressants alleviate depression-related behaviours by specifically counteracting the NLRP3 inflammasome signalling pathway. The immunomodulatory effects of vortioxetine (VTX), a multimodal antidepressant with cognitive benefits, were recently revealed to counter memory impairment induced by a peripheral lipopolysaccharide (LPS) injection 24 hours (h) post-challenge. The potential link between VTX and NLRP3, along with other inflammasomes, remains un-explored.MethodsThe potential link between VTX and NLRP3, along with other inflammasomes, remains unexplored. Hence, adult C57BL/6J male mice (n = 73) were fed with a standard or VTX-enriched diet (600 mg/kg of food, 28 days), injected with LPS (830 μg/kg) or saline, and sacrificed 6/24 h post-LPS. At these time-points, transcriptional effects of LPS and VTX on NLRP3, NLRP1, NLRC4, AIM2 (inflammasomes), ASC and CASP1 (related subunits) and NEK7 mediator (NLRP3 regulator) were assessed in dorsal and ventral hippocampal subregions, frontal-prefrontal cortex and hypothalamus, brain regions serving behavioural-cognitive functions impaired in MDD.ResultsVaried expression patterns of inflammasomes were revealed, with long-term NLRP3 and ASC transcriptional changes observed in response to LPS. It was demonstrated that VTX counteracted the LPS-mediated NLRP3 and ASC upregulation in memory-related brain areas like the dorsal hippocampus at 24 h time-point, potentially via regulating NEK7 expression. No VTX-mediated transcriptional effects were observed on other inflammasomes, reinforcing a potentially specific modulation on the NLRP3 inflammasome signalling pathway.ConclusionThus, a novel VTX molecular mechanism in modulating the NLRP3 inflammasome in a time- and area-specific manner in the brain was highlighted, with significant clinical implications in treating depression and cognitive impairments.
Keywords: hippocampus